Synthesis of The Tangerine-based Cdots and AgNp-Cdots Composite (Indonesian Journal of Chemical Science, 2022)
Silver nanoparticles (AgNp) have been widely developed, one of which is an antibacterial agent. The ability of AgNp to inhibit bacteria is unquestionable. These properties and characteristics can be studied further by adding defects. The defect used is Cdots from tangerines. Cdots are new materials that can be synthesized from natural materials and have unique properties. AgNp itself was synthesized by the chemical reduction method with sodium citrate as a reducing agent, while Cdots was synthesized by hydrothermal method. The results of the synthesis were analyzed using the Fourier Transform Infrared (FT-IR) method. Absorption appears at a wave number of 1637 cm-1 which indicates the presence of C=C, C=O bonds which are characteristic of Cdots. For AgNp, absorption appears at a wave number of 593.11 cm-1 which indicates the presence of Ag vibrations. Analysis with UV-Vis spectrophotometer gave the results at a wavelength of 431 nm absorbance AgNp-Cdots of 0.723 and a wavelength of 422 nm AgNp absorbance of 0.285. The results of the Particle Size Analyzer (PSA) analysis showed that AgNp-Cdots had an average size of 38.7 nm with a PI of 0.499 and pure AgNp of 51.8 nm with a PI of 0.566. Antibacterial activity of AgNp-Cdots against E. coli bacteria showed an inhibition zone of 2 mm while AgNp showed an inhibition zone of 5 mm.